Population‐based metagenomics analysis reveals altered gut microbiome in sarcopenia: data from the Xiangya Sarcopenia Study. Issue 5 (18th July 2022) - Wang, Yilun; Zhang, Yuqing; Lane, Nancy E.; Wu, Jing; Yang, Tuo; Li, Jiatian; He, Hongyi; Wei, Jie; Zeng, Chao; Lei, Guanghua
Abstract: Background: Several studies have examined gut microbiota and sarcopenia using 16S ribosomal RNA amplicon sequencing; however, this technique may not be able to identify altered specific species and functional capacities of the microbes. We performed shotgun metagenomic sequencing to compare the gut microbiome composition and function between individuals with and without sarcopenia. Methods: Participants were from a community‐based observational study conducted among the residents of rural areas in China. Appendicular skeletal muscle mass was assessed using direct segmental multi‐frequency bioelectrical impedance and grip strength using a Jamar Hydraulic Hand dynamometer. Physical performance was evaluated using the Short Physical Performance Battery, 5‐time chair stand test and gait speed with the 6 m walk test. Sarcopenia and its severity were diagnosed according to the Asian Working Group for Sarcopenia 2019 algorithm. The gut microbiome was profiled by shotgun metagenomic sequencing to determine the microbial composition and function. A gut microbiota‐based model for classification of sarcopenia was constructed using the random forest model, and its performance was assessed using the area under receiver‐operating characteristic curve (AUC). Results: The study sample included 1417 participants (women: 58.9%; mean age: 63.3 years; sarcopenia prevalence: 10.0%). β‐diversity indicated by Bray–Curtis distance (genetic level: P  = 0.004; taxonomic level of species: P  = 0.020), but not α‐diversity indicated by Shannon index (genetic level: P  = 0.962; taxonomic level of species: P  = 0.922), was significantly associated with prevalent sarcopenia. After adjusting for potential confounders, participants with sarcopenia had higher relative abundance of Desulfovibrio piger ( P  = 0.003, Q = 0.090), Clostridium symbiosum ( P  < 0.001, Q = 0.035), Hungatella effluvii ( P  = 0.003, Q = 0.090), Bacteroides fluxus ( P  = 0.002, Q = 0.089), Absiella innocuum ( P  = 0.002, Q = 0.072), Coprobacter secundus ( P  = 0.002, Q = 0.085) and Clostridium citroniae ( P  = 0.001, Q = 0.060) than those without sarcopenia. The relative abundance of six species ( Desulfovibrio piger, Clostridium symbiosum, Hungatella effluvii, Bacteroides fluxus, Absiella innocuum, and Clostridium citroniae ) was also positively associated with sarcopenia severity. A differential species‐based model was constructed to separate participants with sarcopenia from controls. The value of the AUC was 0.852, suggesting that model has a decent discriminative performance. Desulfovibrio piger ranked the highest in this model. Functional annotation analysis revealed that the phenylalanine, tyrosine, and tryptophan biosynthesis were depleted ( P  = 0.006, Q = 0.071), while alpha‐Linolenic acid metabolism ( P  = 0.008, Q = 0.094), furfural degradation ( P  = 0.001, Q = 0.029) and staurosporine biosynthesis ( P  = 0.006, Q = 0.072) were enriched in participants with sarcopenia. Desulfovibrio piger was significantly associated with staurosporine biosynthesis ( P  < 0.001). Conclusions: This large population‐based observational study provided empirical evidence that alterations in the gut microbiome composition and function were observed among individuals with sarcopenia.